2019
DOI: 10.1021/acs.iecr.8b05043
|View full text |Cite
|
Sign up to set email alerts
|

Calibration Model Building for Online Monitoring of the Granule Moisture Content during Fluidized Bed Drying by NIR Spectroscopy

Abstract: For monitoring the granule moisture content during a fluidized bed drying (FBD) process, a calibration model building method is proposed for in situ measurement using the near-infrared (NIR) spectroscopy. It is found that the FBD operating conditions such as the chamber temperature and heating power have a nonnegligible impact on the NIR model prediction of granule moisture. By combining these operating variables with the measured NIR spectra for model calibration, the prediction accuracy for online measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A brief introduction of the working mechanism and offline measurement by the losson-drying (LOD) method for validation can be found in a previous work. 4 2.2. Drying Materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief introduction of the working mechanism and offline measurement by the losson-drying (LOD) method for validation can be found in a previous work. 4 2.2. Drying Materials.…”
Section: Methodsmentioning
confidence: 99%
“…More details about the experimental conditions and data collection are provided in the previous work. 4 Figure 2 illustrates the sampled NIR spectra and granule moisture content from batch 1. It is seen from the plot of granule moisture content that the FBD process basically consists of two phases, that is, underdrying and postdrying phases.…”
Section: Methodsmentioning
confidence: 99%
“…10 They can also reduce variables that do not correctly characterize the chemical properties of measured objects; this is called outlier removal. 11,12 Other pre-processing methods can also reduce the dimensionality of spectral data. 13 Based on the pre-processed data, classification and regression techniques are employed for qualitative and quantitative analyses.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that PLS is better than the other methods as the former has the minimum prediction error. With the prior process knowledge, some process variables were found to have a great effect on the final product quality, which were used for model building by combination with NIR spectroscopy [5] [15]. However, most existing calibration modeling methods are linear models.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above analysis, the dimension of spectral data should be reduced before modeling. Meanwhile, the nonlinear relationship should be taken into consideration in order to obtain more accurate calibration performance [4] [15]. In most published calibration methods, the modeling data are analyzed discretely and discretely by the traditional multivariate statistical methods, without considering the implied continuous property within the variables.…”
Section: Introductionmentioning
confidence: 99%